2021
DOI: 10.1039/d1ra02073k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lattice distortion, yield strength, critical resolved shear stress, and improving mechanical properties of transition-metals doped CrCoNi medium entropy alloy

Abstract: The effect of transition-metals (TM) addition on the mechanical properties of CrCoNi medium entropy alloys (MEAs) was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…1), the addition of Y causes a shift in the positions of the FCC reflections towards the lower angles due to the dissolution of Y in the matrix. This suggests a lattice distortion in the FCC crystal structure, and hence, an inc-rease in the mechanical properties (44) due to the much larger atomic radius of Y as compared to the elements in the matrix (45). Secondly, the formation of the second phase causes a dramatic increase in the mechanical properties of the HEAs as reported in the previous studies (14,32,42).…”
Section: The Evolution Of Mechanical Propertiesmentioning
confidence: 58%
“…1), the addition of Y causes a shift in the positions of the FCC reflections towards the lower angles due to the dissolution of Y in the matrix. This suggests a lattice distortion in the FCC crystal structure, and hence, an inc-rease in the mechanical properties (44) due to the much larger atomic radius of Y as compared to the elements in the matrix (45). Secondly, the formation of the second phase causes a dramatic increase in the mechanical properties of the HEAs as reported in the previous studies (14,32,42).…”
Section: The Evolution Of Mechanical Propertiesmentioning
confidence: 58%
“…The lattice distortion is a basic prominence of a crystal. Doping element can induce either lattice expansion or contraction, according to its relative atomic size, crystal structure and chemical bond with respect to undoped element [39,40]. In Ba 2 TbBi (1−x) Sb x O 6 (x = 0, 0.5) perovskites lattice distortion occurs due to the departure or outgoing of atoms location from the pure lattice due to 50% Sb doping in place of Bi.…”
Section: Lattice Distortionmentioning
confidence: 99%
“…Lattice distortion enhances the internal energy and the microscopic stress of the material. It resists the dislocation glide deformation, making the material strength and hardness increase [40].…”
Section: Lattice Distortionmentioning
confidence: 99%
“…Since 2018, the number of reports on the CoCrNi alloy has increased dramatically. The understanding of various aspects of the alloy has been gradually deepened, including lattice distortion (LD) [34][35][36] , stacking fault energy (SFE) [37][38][39][40] and the critical shear stress of dislocations and twins [41] . The dislocation, twinning, phase transformation and even texture during deformation have been systematically studied [42][43][44][45][46][47] .…”
Section: Development Of Cocrni Alloymentioning
confidence: 99%
“…Jian et al [34] investigated the role of LD and SRO in the nucleation and evolution of dislocations and nanotwins in single-crystal and nanocrystalline CoCrNi alloys. They showed that YSs were determined by the strain to nucleate the Shockley partial dislocations.…”
Section: Lattice Distortionmentioning
confidence: 99%